2013
DOI: 10.1017/s104795111300142x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and emotional outcomes in school-aged children after surgery or transcatheter closure treatment for ventricular septal defect

Abstract: School-aged children who underwent repair of ventricular septal defect regardless of the type of treatment (surgery or transcatheter closure) exhibit internalising behavioural problems. Risk factors for developing problems are young age, scarring, post-operative atrioventricular block, and maternal anxiety. In particular, maternal anxiety is the most important risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 26 publications
2
43
0
2
Order By: Relevance
“…The correspondence in anxiety measures between mother and child was not found in the comparison group. Similarly, Guan et al . found that maternal anxiety was the most important risk factor for internalizing symptoms in a 6‐ to 13‐year‐old cohort with VSD.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…The correspondence in anxiety measures between mother and child was not found in the comparison group. Similarly, Guan et al . found that maternal anxiety was the most important risk factor for internalizing symptoms in a 6‐ to 13‐year‐old cohort with VSD.…”
Section: Discussionmentioning
confidence: 82%
“…The correspondence in anxiety measures between mother and child was not found in the comparison group. Similarly, Guan et al 7 found that maternal anxiety was the most important risk factor for internalizing symptoms in a 6-to 13-year-old cohort with VSD. In addition, Perricone et al 27 emphasized that the post-surgery development of children with CHD primarily depends on parental variables rather than on medical factors.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations